2020
DOI: 10.1108/ijse-03-2020-0153
|View full text |Cite
|
Sign up to set email alerts
|

Household wealth and maternal health: evidence from Ghana

Abstract: PurposeIn 2016, the World Health Organization (WHO) revised upwards the recommended contacts for antenatal care (ANC) by expectant mothers with a health provider from a minimum of four to eight over the pregnancy period. Although Ghana is yet to adopt the new recommendation, some women choose to adhere to the new protocol because of its enormous health benefits to the expecting mother and the unborn child. As part of ANC, family planning services are also provided to ensure child spacing and birth control. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…We noted that maternal education has significant positive impacts on both ≥ 4 ANC and the newly recommended ≥ 8 antenatal contacts. Our finding of a significant positive association between maternal education and ≥ 4 and the recommended ≥ 8 antenatal contacts conforms to past studies, both for Nigeria and elsewhere ( 7 , 17 , 20 , 28 30 ). However, this finding contradicts the reports made by some other studies conducted in Nigeria and elsewhere ( 2 , 31 ).…”
Section: Discussion Of the Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…We noted that maternal education has significant positive impacts on both ≥ 4 ANC and the newly recommended ≥ 8 antenatal contacts. Our finding of a significant positive association between maternal education and ≥ 4 and the recommended ≥ 8 antenatal contacts conforms to past studies, both for Nigeria and elsewhere ( 7 , 17 , 20 , 28 30 ). However, this finding contradicts the reports made by some other studies conducted in Nigeria and elsewhere ( 2 , 31 ).…”
Section: Discussion Of the Resultssupporting
confidence: 92%
“…We further observed that access to media showed increased odds for undertaking ≥ 4 and ≥ 8 ANC contacts, which conform to studies in Benin Republic (7), a Ghanaian study (17), an Ethiopian study (30,33), India study (34), Bangladesh (35), and rural Malawi (36). The reason for this could be that frequently listening to the radio and watching television will increase the literacy of a person, which has been noted as a key determinant of maternal care utilization (17). According to Afu-Mensah et al (37) information education through media influences the use of health services (17).…”
Section: Discussion Of the Resultssupporting
confidence: 90%
See 3 more Smart Citations